Spectrum of Mycotic corneal ulcers in Mid Western peripheral region of Terrain belt of Nepal and Indo-Nepal Border - Bastola, P; Mishra, A; Chaudhary, N; Nath, HK; Mehrotra, AN (Nepal Journal of Medical Sciences, 2013)
Background: The study was set in two different tertiary eye care hospitals of Nepal. The study area covered a large population of mid western, far western peripheral terrain regions of Nepal as well as the corresponding Indo-Nepal border. Looking at the high prevalence of mycotic corneal ulcers in the region, the study aimed to find out the pattern of culture proven fungal corneal isolates in diagnosed cases of mycotic corneal ulcers. Methods: A prospective hospital based study was carried out on 2768 consecutive patients presenting with corneal ulcer in the outpatient department of Ophthalmology in Nepalgunj Medical College and Nepalgunj Eye Hospital, Nepalgunj Nepal from July, 2011 to July, 2012. Patient particulars with regard to the socio demographic data, predisposing risk factors, prior treatment modalities, laboratory results and the distribution pattern of culture proven fungal isolates were analyzed. Results: Diagnosis of various types of pure fungal keratitis was established post investigations in 760 (27.45%) of all patients. Men 444 (58.42%) were more commonly affected than women. The young adults age group of 31-40 years was most commonly involved 220 (28.94%) in number. Trauma or injury to cornea 431 (56.71%) was the commonest predisposing risk factor. Fusarium species (Fusarium spp.) were the commonest fungal isolates accounting for 287 (37.76%) of diagnosed fungal ulcer cases, followed by curvularia 136 (17.89%). Conclusion: Fusarium species are the commonest fungal isolates in cases of fungal corneal ulcer in mid western peripheral terrain belt of Nepal followed by curvularia and unidentified dematiaceous fungi. Nepal Journal of Medical Sciences | Volume 02 | Number 01 | Jan-Jun 2013 | Page 42-47 DOI: http://dx.doi.org/10.3126/njms.v2i1.7651